2022
DOI: 10.3389/fonc.2022.858598
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circLMO1 Suppresses Cervical Cancer Growth and Metastasis by Triggering miR-4291/ACSL4-Mediated Ferroptosis

Abstract: BackgroundA number of studies have demonstrated that circular RNA (circRNA) plays a critical role in tumorigenesis and tumor progression. However, the biological effects of most circRNAs on cervical cancer remain unclear. Hsa_circ_0021087 (thereafter named circLMO1) is a circRNA generated from the circularization of exon 2 and exon 3 of LIM Domain Only 1 (LMO1) and first identified as a tumor suppressor in gastric cancer. We aimed to identify the role of circLMO1 in cervical cancer progression.MethodsCircLMO1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 43 publications
0
55
0
Order By: Relevance
“…Moreover, previous studies have clarified that circular RNA (circRNA) could participate in inhibiting tumorigenesis and tumor progression. Ou et al (2022) found circular RNA (CircLMO1) could inhibit cervical cancer proliferation by activating ACSL4-induced ferroptosis, and could be a promising anti-cancer biomarker for cervical cancer. As for chemotherapy treatment of cervical cancer, ACSL4-mediated ferroptosis could play an important role in propofol synergistic anticancer effects with paclitaxel ( Zhao et al, 2022 ).…”
Section: Acyl-coa Synthetase Long-chain Family 4 and Cancermentioning
confidence: 97%
“…Moreover, previous studies have clarified that circular RNA (circRNA) could participate in inhibiting tumorigenesis and tumor progression. Ou et al (2022) found circular RNA (CircLMO1) could inhibit cervical cancer proliferation by activating ACSL4-induced ferroptosis, and could be a promising anti-cancer biomarker for cervical cancer. As for chemotherapy treatment of cervical cancer, ACSL4-mediated ferroptosis could play an important role in propofol synergistic anticancer effects with paclitaxel ( Zhao et al, 2022 ).…”
Section: Acyl-coa Synthetase Long-chain Family 4 and Cancermentioning
confidence: 97%
“…Tumor suppressive roles: circLMO1 antagonized miR-4192-mediated targeting of ACSL4 in cervical cancer cells (Ou et al, 2022). circLMO1 potently hampered proliferation and invasion capacities of CaSki cells, whereas ACSL4 depletion or miR-4291 overexpression exerted inhibitory effects on circLMO1mediated tumor suppressive effects.…”
Section: Role Of Circular Rnas In the Regulation Of Ferroptosismentioning
confidence: 98%
“…Levels of circP4HB and SLC7A11 were increased in the tumor xenografts in mice injected with circP4HBoverexpressing cells (Pan et al, 2022). circ-BGN, an oncogenic circular RNA is frequently overexpressed in trastuzumab resistant-breast cancer cells (Wang et al, 2022). OTUB1 is a deubiquitinating enzyme and it de-ubiquitinates SLC7A11.…”
Section: Role Of Circular Rnas In the Regulation Of Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…CircLMO1 overexpression inhibited the growth and metastasis of CC cells both in vitro and in vivo whereas its knockdown increased the proliferation and invasion of CC cells. Mechanistically, CircLMO1 functioned as a competitive endogenous RNA (ceRNA) by sponging miR-4192 to inhibit target gene ACSL4, suggesting that it might be a promising biomarker for the clinical management of CC [ 91 ]. In depth research suggests that several miRNAs play a prominent role in CC suppression, many of which are listed in Table 2 .…”
Section: Expression and Function Of Ncrnas In CCmentioning
confidence: 99%